Preventing lethal school violence - Daniels, Jeffrey A. (Advancing responsible adolescent development, 2011)
Introduction to lethal school violence -- Costs of lethal school violence -- Bullying and lethal acts of school violence -- Averted school rampages -- Successfully resolved barricaded captive events -- Building a positive school climate -- The safe school communities model